The prevalence and potential implications of microplastic contamination in marine fishes from Xiamen Bay, China. (January 2022) - Wei, Lili; Wang, Daling; Aierken, Reyilamu; Wu, Fuxing; Dai, Yufei; Wang, Xianyan; Fang, Chao; Zhao, Liyuan; Zhen, Yu
Abstract: The wide presence of microplastics (MPs) in the ocean leads their exposure on marine fish. MP contamination was reported for the gastrointestinal tracts and gills of 117 marine fishes attributed to nine species from Xiamen Bay, a special economic zone in China. Among species, MP abundance ranged from 1.07 items individual −1 to 8.00 items individual −1 . Fibers dominated MP shapes, accounting for 59.03% of all MPs. Polymer composition was dominated by polyamide (26.97%) and rayon (17.56%). MPs were most commonly (55.22%) transparent, and most (77.61%) were < 1 mm in size. Our report represents the first of MP contamination in wild marine fish from Xiamen Bay, which we determine to be at an intermediate to slightly higher level compared with levels reported elsewhere, and provides further insights into potential risks of MPs pose to fish and human health. Highlights: Microplastics were firstly reported present in wild fish from Xiamen Bay. Microplastics abundance ranged from 1.07 items individua −1 to 8.00 items individual −1 . Microplastics abundance in the gastrointestinal tracts was higher than in gills. The occurrence of Microplastics in seafood for human consumption is cause for concern.